Globalisasi Mengubah Konsep Negara, Teritori, Kedaulatan : Integrasi ALBA sebagai Sovereignty Counter-Balance - Wahyuni Andike; Siti R Susanto (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
Globalization as a dynamic process has contributed to change and downgrade the power of. Most state experience various development regarding cross-border interaction, such as in economy, politics, and culture. Although the Westphalia Treaty of 1648 was a turning point where loyalty of people must be given to the state, yet it is shown that the power of state does no longer exist as the only political power. Venezuela’s Populist economic policies under Nicolas Maduro considered as failed-state management which lead the country reaching equitable welfare. Regarding Venezuela from the start in the ALBA (the Bolivarian Alliance for the peoples of our America), it has been able to help a little compilation of this country to improve the crisis, asking that the ALBA here try to be seen as " Sovereignty Counter-Balance". Domestic problems that continue to make the Venezuelan exodus abroad. This national crisis and massive migration have had international implications. And the countries that have helped overcome this are Ecuador and Colombia. This paper examines the interrelationship between the causes of the Venezuelan crisis and its consequences, as well as the reactions of other countries. In this paper the author analyzes and explains the link between the Venezuelan crisis and its effects, as well as the reactions, attitudes and role of neighboring countries in this case Ecuador and Colombia. The purpose of this study was to find out how ALBA was able to maintain the harmony and position of domestic interdependence by not eliminating the existence and authority of member states. This writing uses qualitative descriptive methods with data collection using literature studies. After reviewing, analyzing some literature concluded that ALBA can be a catalyst for Latin America to strengthen relations and unite views in the face of such dynamic global problems.